Mobile Learning in a Human Geography Field Course. Issue 2 (3rd March 2016) - Jarvis, Claire; Tate, Nicholas; Dickie, Jennifer; Brown, Gavin
Abstract : This article reports on reusable mobile digital learning resources designed to assist human geography undergraduate students in exploring the geographies of life in Dublin. Developing active learning that goes beyond data collection to encourage observation and thinking in the field is important. Achieving this in the context of large class sizes presents several challenges. Combining in situ learning with spatially accurate historical and contemporary multimedia, a set of location-aware digital mobile tools, or mediascapes, was developed. How scaffolding can be achieved in such a context, focusing on the development of students' observational, enquiry, and thinking skills in the field was explored.